Lung ultrasound in children - Maciej Przybył; Edyta Machura (Termedia Publishing House, 2022)
Lung ultrasound (LUS) plays an increasingly important role in the diagnosis of chest diseases, and it is often called "the stethoscope of the 21st century". It is a quick, inexpensive, radiation-free tool with a point-of-care option allowing for safe screening and/or follow-up. This paper presents the scanning technique, normal lung image, detectable pathologies, and exemplary applications in different disorders. Although lung ultrasound is of particular importance for the diagnosis of pneumonia in children, it has not been included in official guidelines so far. Advantages of lung ultrasound and advances in medical technology should increase the popularity of this technique as a complement to physical examination.